(untitled) (Cybersecurity and Network Defense Research, 2021)
Identity Federation is a crucial supporter for secure and seamless authentication across multiple cloud environments which makes interoperability and access management in cross cloud workflows. But achieving robust identity federation in heterogeneous cloud ecosystem creates number of technical and operation challenges such as protocol standardization, trust establishment, security vulnerabilities, and performance overhead. This paper aims to explore the in-depth challenges, analysing authentication mechanism such as Security Assertion Markup Language (SAML), OpenID Connect (OIDC), and OAuth 2.0.